Dependence of biological activity of surfactants synthesized by Rhodococcus erythropolis IMV Ac-5017 on physiological state of yeast inducer - Okhmakevych, Anastasiia; Pirog, Tatiana; Kliuchka (Nykytyuk), Lilia (My University, 2025)
Surfactants synthesized by Rhodococcus erythropolis IMV Ac-5017 can be used as antibiofilm agents due to their antimicrobial activity. The antimicrobial activity of surfactants can be increased by adding inducers to the R. erythropolis cultivation medium. Materials and methods. R. erythropolis IMV Ac-5017 was cultivated in ethanol-containing medium with Saccharomyces cerevisiae BTM-1 as an inducer. Surfactant concentrations were determined gravimetrically. The minimum inhibitory concentration was used to assess the antimicrobial activity of surfactants, and their ability to disrupt biofilms was determined by the spectrophotometric method. Results and discussion. The antimicrobial activity of surfactants synthesized by R. erythropolis IMB Ac-5017 and their ability to destroy biofilms can be significantly increased by introduction of S. cerevisiae BTM-1 cells being at different physiological states into the medium for cultivation. The surfactants synthesized by R. erythropolis IMV Ac-5017 in the presence of live S. cerevisiae BTM-1 cells, as well as the corresponded supernatant, exhibited the highest biological activity. Under these conditions, surfactants synthesized demonstrated the minimum inhibitory concentrations, which were 3.6–240 times lower compared to the values reported for surfactants produced in the medium without an inducer. Surfactants synthesized in the presence of inducers destroyed single- and dual-species biofilms by 9-59% and 1-29% more effectively, respectively, than those obtained in the medium without them. Surfactants of R. erythropolis IMV Ac-5017 obtained with inactivated inducer cells were less active, probably because proteins of inducer cells could be denatured during autoclaving. Biological activity of the surfactants produced in the presence of the yeast inducer was more specific towards yeast test cultures, which can be explained by the nature of the studied inducer. Conclusion. The addition of the yeast inducer into the medium for cultivation of R. erythropolis IMV Ac-5017 contributed to significant increase of biological activity of surfactants compared to those synthesized in the medium without an inducer.

Поверхнево-активні речовини, синтезовані Rhodococcus erythropolis IMV Ac-5017, можуть бути використані як антибіоплівкові агенти завдяки їхній антимікробній активності. Антимікробну активність поверхнево-активних речовин можна підвищити, додаючи індуктори до середовища культивування R. erythropolis. Матеріали та методи. R. erythropolis IMV Ac-5017 культивували в етанолвмісному середовищі з Saccharomyces cerevisiae BTM-1 як індуктором. Концентрації поверхнево-активних речовин визначали гравіметрично. Мінімальну інгібуючу концентрацію використовували для оцінки антимікробної активності поверхнево-активних речовин, а їх здатність руйнувати біоплівки визначали спектрофотометричним методом. Результати та обговорення. Антимікробну активність поверхнево-активних речовин, синтезованих R. erythropolis IMB Ac-5017, та їх здатність руйнувати біоплівки можна значно підвищити, вводячи в середовище для культивування клітин S. cerevisiae BTM-1, що перебувають у різних фізіологічних станах. Поверхнево-активні речовини, синтезовані R. erythropolis IMV Ac-5017 у присутності живих клітин S. cerevisiae BTM-1, а також відповідний супернатант, продемонстрували найвищу біологічну активність. За цих умов синтезовані поверхнево-активні речовини продемонстрували мінімальні інгібуючі концентрації, які були в 3,6–240 разів нижчими порівняно зі значеннями, зареєстрованими для поверхнево-активних речовин, отриманих у середовищі без індуктора. Поверхнево-активні речовини, синтезовані у присутності індукторів, руйнували одно- та двовидові біоплівки на 9-59% та 1-29% ефективніше відповідно, ніж ті, що були отримані у середовищі без них. Поверхнево-активні речовини R. erythropolis IMV Ac-5017, отримані з інактивованими клітинами-індукторами, були менш активними, ймовірно, тому, що білки клітин-індукторів могли денатуруватися під час автоклавування. Біологічна активність поверхнево-активних речовин, отриманих у присутності індуктора дріжджів, була більш специфічною до тест-культур дріжджів, що можна пояснити природою досліджуваного індуктора. Висновки. Додавання індуктора дріжджів до середовища для культивування R. erythropolis IMV Ac-5017 сприяло значному підвищенню біологічної активності поверхнево-активних речовин порівняно з тими, що синтезувалися у середовищі без індуктора.
Keywords: індуктор; антимікробна активність; деструкція біоплівок; кафедра біотехнології і мікробіології; Rhodococcus erythropolis IMB Ac-5017; surfactants; inducer; antimicrobial activity; biofilm destruction; biofilm destruction